2022-RA-1591-ESGO Major determinants of survival in recurrent endometrial cancer: The role of secondary cytoreductive surgery and relapse pattern. A Multicenter Study. (20th October 2022) - Vargiu, Virginia; Rosati, Andrea; Capozzi, Vito Andrea; Gioè, Alessandro; Restaino, Stefano; Foresta, Aniello; Berretta, Roberto; Scambia, Giovanni; Cosentino, Francesco; Fanfani, Francesco
Abstract : Introduction/Background: Despite advances in endometrial cancer treatments and knowledge, survival for recurring cancers remains poor.In this study, we evaluated the impact of clinical-histological-radiological variables of patients with endometrial cancer recurrence (ECR) on overall-survival (OS), and specifically, we evaluated the impact of secondary-cytoreductive-surgery (SCS) with the achievement of complete gross resection (CGR) on different types of relapses. Methodology: Multicenter-retrospective analysis of patients with ECR. Results: Three-hundred-thirty-one patients were retrieved. At Cox-regression multivariate analysis, age ≥75 yr (HR: 2.056, p=0.003), advanced prognostic risk-group at initial diagnosis (HR: 3.240, p=0.007) and the presence of multiple site relapses (HR: 1.589, p=0.045) resulted to be statistically significant factors for reduced OS, while SCS and the disease-free survival (time from diagnosis to I relapse) were predictors of improved OS (respectively HR: 0.161, p<0.001, HR: 0.972, p<0.001) (Figure-1 ).Survival analysis using the Kaplan-Meier method showed that patients with single-site relapse had an improved OS than patients with multiple-site relapses (log-rank p<0.001) (Figure-1 ).Further stratifying the population on the surgery performed (SCS with CGR vs SCS with residual tumor (RT)> 0 or other secondary treatment), the Kaplan-Meier curves showed that achieving CGR conferred a statistically significant OS benefit for patients with single site metastases (p=0.044) and a trend towards better survival for patients with multiple site metastases (p=0.090) ( figure 1 ). Conclusion: SCS confirmed to be a statistically independent relevant factor for better OS along with DFS in ECR, while age≥75 years, the advanced prognostic risk group and the presence of multiple site relapses were significant factors for decreased OS.In addition, the achievement of CGR conferred a statistically significant survival advantage on patients with single-site recurrence compared to patients not operated or operated with RT>0, while a trend toward better survival could be identified in patients with multiple-site relapses when completely gross resected.